(untitled) (Palíndromo, 2021)
When the score stops from being an inscription based on representatives aims, it assumes a more operational direction, intended for actions. Is is not by chance that the score as a form was widely used in the 60s avant gard. These artists sought to reconfigure the notion around the art object, who was before very derivative, starting from more performative prepositions. The landmark of the formal autonomy gain of the score is located in the work of the composer John Cage - his position of converting music into sound and vice versa ends up inaugurating a regime where everything sounds. The Fluxus movement is inscribed in an aesthetic dynamic of ritualizing everyday habits, prolonging the common occurrences for the temporalities of events. In this paper I try to think about the theoretical approaches between both, thinking from the perspective of language. The Event Scores, so much as John Cage, handled a singular and performative temporalitie in relation to writing, reading and also in relation to listening.